Геотермічні умови і структура земної кори північно-західних Карпат - Кутас, Р.І. (Геоінформатика, 2015)
Наведено результати спільного аналізу сейсмічних і геотермічних даних уздовж двох профілів сейсмічного зондування (CEL 05 і PANCAKE), що перетинають Західні (на території Польщі) і північну частину Східних Карпат (на території України). Товщина земної кори змінюється від 24—25 км у Паннонському басейні до 45— 50 км у межах Транс’європейської сутурної зони (ТЄСЗ) та Східноєвропейського кратону (СЄК). При цьому змінюється і структура земної кори. Тришарова кристалічна кора, типова для докембрійської платформи, трансформується у двошарову в зоні ТЄСЗ на профілі CEL 05 і під прогином Східних Карпат на профілі PANCAKE. У прогині під Зовнішніми Карпатами товщина осадового шару сягає 18—20 км. Його верхня частина (8—10 км) представлена насувом флішоїдних утворень крейди — раннього міоцену, а нижня — очевидно, осадовими породами від палеозою до неогену. Густина теплового потоку уздовж цих профілів змінюється від 35—40 мВт/м² у межах СЄК до 100—130 мВт/м² у Паннонському басейні. Аналіз геотермічних даних і 2D моделювання дають змогу пов’язати неоднорідності теплового поля з особливостями геодинамічної еволюції регіону від пізнього протерозою до теперішнього часу. Формування локальних і зональних аномалії залежить від будови земної кори, розподілу в ній радіогенних джерел тепла і зміни умов теплоперенесення. Високі теплові потоки в Паннонському басейні асоціюються з підняттям астеносфери до глибин 40—50 км наприкінці олігоцену — в міоцені. Приводятся результаты совместного анализа сейсмических и геотермических данных вдоль двух профилей сейсмического зондирования (CEL 05 и PANCAKE), пересекающих Западные (на территории Польши) и северную часть Восточных Карпат (на территории Украины). Мощность земной коры изменяется от 24-25 км в Паннонском бассейне до 45-50 км в пределах Трансъевропейской сутурной зоны (ТЕСЗ) и Восточно-Европейского кратона (ВЕК). При этом изменяется и структура земной коры. Трехслойная кристаллическая кора, типичная для докембрийской платформы, трансформируется в двухслойную в зоне ТЕСЗ на профиле CTL 05 и под прогибом Восточных Карпат на профиле PANCAKE. Под Внешними Карпатами мощность осадочного слоя достигает 18-20 км. Его верхняя часть (8-10 км) представлена надвигом флишоидных образований мела - раннего миоцена, а нижняя, очевидно, осадочными породами от палеозоя до неогена. Плотность теплового потока вдоль этих профилей изменяется от 35-40 мВт/м² в пределах ВЕК до 100-130 мВт/м² в Паннонском бассейне. Анализ геотермических данных и 2D моделирование позволяют увязать неоднородности теплового поля с особенностями геодинамической эволюции региона от позднего протерозоя до настоящего времени. Локальные и зональные аномалии связаны со строением земной коры, распределением в ней радиогенных источников тепла и изменением условий теплопереноса. Высокие тепловые потоки в Паннонском бассейне ассоциируются с поднятием астеносферы до глубин 40-50 км в конце олигоцена-миоцене. Purpose. The main objective of this study is to analyze the features of the crustal structure and its thermal state along two transects crossing the northern part of the Carpathian and Pannonian region, using new seismic data and the results of the heat flow measurements in the vicinity of profiles (corrected for relief, paleoclimate and thrust effects). This region was investigated by a dense system of deep seismic sounding profiles (experiment CELEBRATION 2000), extended from the Pannonian Basin to the European Paleozoic Platform in the north and to the East European Craton in the northeast or east. The resulting seismic models reveal complex structure in the crust and large variations in the depth of Moho discontinuity (25-48 km). The heat flow density changes from 35 to 130 mW/m2. This paper focuses on the southern and central parts of the CEL 05 (in Poland) and PANCAKE (in Ukraine) profiles crossing the Carpathian and Pannonian regions. Findings. The CEL 05 profile starts in the Pannonian basin and crosses the Inner Carpathians, Pieniny Klippen Belt, Outer Western Carpathians, Trans-European Suture Zone, including Malopolska and Lysogory tectonic units, and the slope of the East European Craton with the Lublin Trough. The thickness of crystalline crust increases along profile from the Pannonian basin (23-30 km) to the Outer Western Carpathians (30-35 km), Trans-European Suture Zone and East European Craton (42—50 km). The crystalline crust is two-layered beneath the Pannonian basin and Outer Western Carpathians (V = 5,9—6,2 km/s and 6,5—6,8 km/s, respectively), while beneath the Trans-European Suture Zone and East European Craton margin the crust is three-layered (6,0—6,4, 6,4—6,7 and 6,7—7,0 km/s, respectively), which that is typical for cratonic areas. Subcrustal velocities increase from 7,8—8,0 km/s in the PB to 8,1—8,25 in the East European Craton. The PANCAKE profile crosses the Pannonian Basin, Transcarpathian Trough, Outer East Carpathians, Carpathian Foredeep and East European Craton (L’viv Paleozoic Trough). There are no substantial differences in the crustal structure as compared to CEL 05 profile, but three-layered crystalline crust (42—48 km in thickness) in the PANCAKE profile is observed beneath the Carpathian Foredeep and Outer East Carpathians, and a two-layered crust (25—30 km) remains beneath the Pannonian Basin and Transcarpathian Trough. The prominent crustal tectonic feature of both profiles is a zone (beneath the Outer East Carpathians and Carpathian Foredeep) with thick sediments with the velocity of V < 5 km/s reaching down to the depth of 18—20 km. Its uppermost part forms the Outer East Carpathians accretionary prism (up to 8 km in thickness). Practical value/implications. The geological and geophysical analysis and mathematical modeling of the thermal field suggest that the basic patterns in the distribution of heat flows are controlled by the regional tectonic zonation, features of the geological development of the region and its crustal structure. High heat flow is provided by high mantle heat flow (35—50 mW/m²). Low heat flow values are typical for the Precambrian and Early Paleozoic areas with a thick crust (40— 50 km). The most part of the Carpathian Foredeep and Outer Carpathians is also characterised by relatively low heat flow density, which may suggest presence of the Precambrian or Early Paleozoic basement beneath the accretionary prism of the Outer Carpathians. An intermediate heat flow density (50—70 mW/m²) is associated with late Paleozoic — early Mesozoic structures (southwestern slope of the Outer East Carpathians and Inner Carpathians). High heat flow in the Pannonian basin is associated with peculiarities of the crust formation at the Alpine stage of evolution, as well as with magmatic activity. The increased heat flow was caused by crust extension and the asthenosphere upraise 25—30 Ma ago. The surface heat flow variations (5—10 mW/m²) in the Folded Carpathians can be caused by lateral changes of radiogenic heat production or thermal conductivity in the sedimentary layer.